2019
DOI: 10.1111/risa.13410
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Quantification of the Population Exposed to Cryptococcus neoformans and Cryptococcus gattii Species Complexes in Europe: Estimating the Immunocompetent and HIV/AIDS Patients Under Risk

Abstract: Cryptococcus is an important fungal pathogen worldwide, causing serious clinical manifestations that can affect immunocompetent patients and can be particularly severe for immunocompromised patients. The Cryptococcus gattii s.s. (AFLP4/VGI), Cryptococcus tetragattii (AFLP/VGIV), Cryptococcus neoformans, and Cryptococcus deneoformans have been isolated from both clinical and environmental sources in Europe. We aim to quantify the people in Europe and the entire Mediterranean area who are under risk associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…The results showed that the geographical areas, compatible with the survival of the fungus, are characterized by a temperate hot climate with warm winters, and dry and hot summers, confirming the endemicity of the pathogen (Cogliati et al, 2017). A further study identified where the potential risk of contact with the fungus is higher and revealed that more than 137 million people are potentially involved (Alaniz et al, 2020). In the last decades, cases of cryptococcosis due to C. gattii VGI in Europe have increased compared to the almost absence of cases reported in the past, with half of the cases occurred in immunocompetent hosts (Andreou et al, 2019;Hagen et al, 2012;Iatta et al, 2012;McCormick-Smith et al, 2015;Passera et al, 2020).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The results showed that the geographical areas, compatible with the survival of the fungus, are characterized by a temperate hot climate with warm winters, and dry and hot summers, confirming the endemicity of the pathogen (Cogliati et al, 2017). A further study identified where the potential risk of contact with the fungus is higher and revealed that more than 137 million people are potentially involved (Alaniz et al, 2020). In the last decades, cases of cryptococcosis due to C. gattii VGI in Europe have increased compared to the almost absence of cases reported in the past, with half of the cases occurred in immunocompetent hosts (Andreou et al, 2019;Hagen et al, 2012;Iatta et al, 2012;McCormick-Smith et al, 2015;Passera et al, 2020).…”
Section: Introductionmentioning
confidence: 69%
“…The Mediterranean coasts are geographical areas with a high density of population and therefore an expansion of the distribution of C. gattii VGI, associated with an increase of its probability of presence in these areas, corresponds to an increase in the risk of contact with the fungus for more than 137 million persons (Alaniz et al, 2020). On the basis of these predictions, an increase of cases of cryptococcosis due to C. gattii VGI is expected in the next decade and a constant monitoring of the epidemiology of this fungal pathogen represents a crucial strategy to detect the onset of future outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial methodological framework presented here was successfully used in a recent study to determine the risk zones in Europe to different cryptococcal pathogens ( Alaniz et al, 2020 ). The suitable geographic areas for C. bacillisporus survival are characterized by scarce or null rainfall during the dry season and moderate rainfall during the cold season, high SR and scarce vegetation corresponding to the warm summer Mediterranean climate present in California and northwestern Mexico ( Acheson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to predict the environmental suitability for the species based on its ecological niche requirements. The spatial prediction of an SDM can be homologated to the potential abundance of organisms ( Phillips et al, 2006 ), and it has proven to generate reliable results for the modeling of infectious disease vectors ( Alaniz et al, 2017 , 2018 , 2020 ). We compiled and systematized an occurrence database consisting of 29 occurrences of C. bacillisporus environmental isolates according to the following criteria: (A) avoiding isolates from humans due to the uncertainty related to the movement of the patient, however we included four human occurrences from Lockhart et al, 2013 which denoted no travel history of patients, (B) excluding those without specific geographical coordinates (latitude and longitude) reducing the uncertainty on the location and (C) excluding the Chilean isolate to predict the distribution based on the source zone niche ( Supplementary Appendix Figure S1 and Supplementary Appendix Table S1 ) ( Pfeiffer and Ellis, 1991 ; Escandón et al, 2006 ; Mazza et al, 2013 ; Singer et al, 2014 ; Springer et al, 2014 ; Espinel-ingroff and Kidd, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation